Fertilización de maíz zea mays l. con bioestimulantes y microorganismos fijadores de nitrógeno en el cantón Balao - Tacuri Guambaña, Pedro Orlando (2012)
Research on Fertilization of maize (Zea mays L.) with biostimulants and nitrogen-fixing microorganisms in the canton Balao, had the following objectives: 1. To evaluate the effect of fertilization and corn biostimulants nitrogen fixing microorganisms 2. Compare the performance of using microorganisms to biostimulants and conventional mineral fertilization and 3. Perform an economic analysis of the treatments. The distributions of the plots were made based on a randomized block design having four treatments and five repetitions, totaling 20 experimental units. The variables analyzed were: plant height at 30.60 and 90 days to the formation of cob, number of ears per plant, pod length, 100-seed weight and yield in kg / ha. We performed site preparation using agricultural machinery and then made the plowing and the outline of the plots.Sowing was done by hand by placing two seeds per hole, leaving about 30 cm between plants and 1 m between furrows. The frequency of irrigation depended mainly on the length of the growing season, rain and soil type. The first irrigation was given to eight days before planting. The application of the fertilizer was applied at seeding performed eight days, then at 20, 50 and 80 days in each treatment. The work-up to control weeds, pests and diseases are periodically made to the needs of the crop. The results showed highly significant in the treatments. Height growth in excelled treatment with urea beating others, different results were obtained in the number of fruits per plant, weight or final yield per hectare where the application of EcosisXXI, followed by the Twin N proved to be the best. The economic benefit was better in the treatment with application of ecosystem XXI.